2018
DOI: 10.1148/radiol.2018180054
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Isocitrate Dehydrogenase Genotype in Brain Gliomas with MRI: Single-Shell versus Multishell Diffusion Models

Abstract: A recent update of the World Health Organization (WHO) classification of brain tumors introduced molecular markers that add greater prognostic accuracy than histopathologic findings alone (1,2). Isocitrate dehydrogenase (IDH) genotype and epigenetic 1p/19q codeletion are two key molecular markers. Patients with IDH wildtype gliomas have a worse prognosis than those with IDHmutant gliomas. Patients with 1p/19q uncodeleted gliomas have a worse prognosis than those with codeleted IDH-mutant gliomas (3). The estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
2
23
0
2
Order By: Relevance
“…Specifically for IDH wild-type glioblastoma, no difference in diffusivity may exist between grades II and IV. 29 Villaneuva-Meyer et al 30 previously assessed ROI-derived minimum, mean, and maximum in WHO grade II gliomas: A minimum ADC threshold of 0.9 Â 10 À3 seconds /mm 2 provided the greatest sensitivity (91%) and specificity (76%) for IDH typing, with an AUC of 0.901. 19 ROI-based minimum ADC analysis was also performed by Wasserman et al 15 with a proposed cutoff point of 0.95Â 10 À3 seconds /mm 2 (sensitivity of 76.9%, specificity of 65.2%, and AUC ¼ 0.711) 13 and by Xing et al 14 with a suggested minimum ADC threshold of 1.01Â 10 À3 seconds /mm 2 (sensitivity of 76.9%, specificity of 82.6%, AUC ¼ 0.87).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for IDH wild-type glioblastoma, no difference in diffusivity may exist between grades II and IV. 29 Villaneuva-Meyer et al 30 previously assessed ROI-derived minimum, mean, and maximum in WHO grade II gliomas: A minimum ADC threshold of 0.9 Â 10 À3 seconds /mm 2 provided the greatest sensitivity (91%) and specificity (76%) for IDH typing, with an AUC of 0.901. 19 ROI-based minimum ADC analysis was also performed by Wasserman et al 15 with a proposed cutoff point of 0.95Â 10 À3 seconds /mm 2 (sensitivity of 76.9%, specificity of 65.2%, and AUC ¼ 0.711) 13 and by Xing et al 14 with a suggested minimum ADC threshold of 1.01Â 10 À3 seconds /mm 2 (sensitivity of 76.9%, specificity of 82.6%, AUC ¼ 0.87).…”
Section: Discussionmentioning
confidence: 99%
“…After the discovery of unique contrast of NODDI maps within gliomas with a 7-T MRI scanner, 45 Maximov et al 46 reported the reliable and feasible differentiation of glioma grading by NODDI parameters. Additionally, although there is no significant additional utility of NODDI for detecting isocitrate dehydrogenase-1 (IDH-1) mutation status in gliomas, 47,48 quantitative NODDI metrics in tumoral and peritumoral regions are suggested to be useful for glioma grading. 48 ND seems to have the best discriminative power for distinguishing normal, tumoral, and peritumoral edematous areas.…”
Section: Tumorsmentioning
confidence: 99%
“…Moreover, Figini et al. ( 34 ) found lower FA and higher MD values in glioma patients with IDH mutations; however, there were no significant result regarding the prediction of 1p19q codeletion.…”
Section: Discussionmentioning
confidence: 95%